ChemInform Abstract: Enantioselective Alkynylation of Benzo[e][1, 2, 3]‐oxathiazine 2, 2‐Dioxides Catalyzed by (R)‐VAPOL‐Zn Complexes: Synthesis of Chiral Propargylic Cyclic Sulfamidates. Issue 46 (November 2015) - De Munck, Lode; Monleon, Alicia; Vila, Carlos; Munoz, M. Carmen; Pedro, Jose R.
Abstract The reaction tolerates aryl, hetaryl, and alkyl substituted acetylenes, and the corresponding products are isolated in moderate to high yields and with moderate to high enantiomeric excess.